Persuasion, Emotion, and Language: The Intent to Persuade Transforms Language via Emotionality - Rocklage, Matthew D.; Rucker, Derek D.; Nordgren, Loran F. (Psychological Science, 2018)
Persuasion is a foundational topic within psychology, in which researchers have long investigated effective versus ineffective means to change other people’s minds. Yet little is known about how individuals’ communications are shaped by the intent to persuade others. This research examined the possibility that people possess a learned association between emotion and persuasion that spontaneously shifts their language toward more emotional appeals, even when such appeals may be suboptimal. We used a novel quantitative linguistic approach in conjunction with controlled laboratory experiments and real-world data. This work revealed that the intent to persuade other people spontaneously increases the emotionality of individuals’ appeals via the words they use. Furthermore, in a preregistered experiment, the association between emotion and persuasion appeared sufficiently strong that people persisted in the use of more emotional appeals even when such appeals might backfire. Finally, direct evidence was provided for an association in memory between persuasion and emotionality.